Composite material for improving sound quality of loudspeaker and loudspeaker

By covering the zeolite particles with zeolite-polymer co-spinning film, the acoustic performance deterioration caused by the prone to breakage of zeolite particles in the speaker and the adsorption of water vapor is solved, and better acoustic effect and durability are achieved.

CN119325055APending Publication Date: 2025-01-17SHENZHEN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423727.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Zeolite particles in existing speakers are prone to breaking, resulting in noise generation, and their adsorption of water vapor leads to deterioration of acoustic performance, making it difficult to effectively utilize their excellent adsorption performance and thermal stability.

Method used

Zeolite particles are coated with zeolite-polymer co-spinning films, and prepared by electrospinning process to form a porous membrane structure, combining zeolite particles and polymer resin materials to improve the protectiveness and acoustic effect of zeolite particles.

Benefits of technology

Effectively prevent zeolite particles from breaking, reducing the system resonance frequency, improving the sound quality of speakers, enhancing high temperature and high humidity resistance, and achieving better acoustic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325055A_ABST
    Figure CN119325055A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material for improving the tone quality of a loudspeaker and the loudspeaker. The composite material comprises zeolite particles, and the zeolite particles are coated with a zeolite-polymer co-spun membrane; the composite material is packaged by a flexible membrane material, on one hand, the flexible membrane material package can be conveniently assembled to the rear cavity of the loudspeaker, and the flexibility of the package can protect zeolite particles from being easily broken when the loudspeaker module is electrified to work or is impacted by falling, or even if the zeolite particles are broken, microsphere chippings and small particles are not easily leaked and enter the magnetic cavity of the loudspeaker; on the other hand, the zeolite material is combined in two forms of particles and membranes by utilizing the excellent adsorption performance and thermal stability of the zeolite, the acoustic effect of the co-spinning membrane material containing the zeolite is close to that of the zeolite particles under unit weight, and the acoustic effect of the co-spinning membrane material containing the zeolite is further improved by co-spinning with the zeolite. The membrane material has the effect of reducing the resonant frequency F0 of the system, and compared with a traditional membrane material, the acoustic effect of the membrane material is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of loudspeakers, and in particular to a composite material for improving the sound quality of a loudspeaker and a loudspeaker. Background Art

[0002] Zeolite, as a porous mineral material, is widely used in various fields due to its excellent adsorption performance and thermal stability. In the field of micro speakers, zeolite is usually directly loaded into the back cavity of the speaker in the form of particles to improve the sound quality. However, the particles are in direct contact with the back cavity shell of the speaker. When the speaker is working, the particles collide violently in the back cavity and are easily broken. After breaking, the small particles are easy to enter other areas of the speaker, causing the speaker to produce noise.

[0003] Therefore, how to better use zeolite particles in speakers has become a technical difficulty in the current field. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a composite material and a loudspeaker for improving the sound quality of a loudspeaker, which can effectively improve the sound quality of the loudspeaker.

[0005] In order to solve the above technical problems, a technical solution adopted by the present invention is:

[0006] A composite material for improving the sound quality of a loudspeaker comprises zeolite particles, wherein the zeolite particles are coated with a zeolite-polymer co-spun membrane.

[0007] Furthermore, the zeolite-polymer co-spun membrane comprises zeolite particles and polymer resin materials.

[0008] Furthermore, the zeolite-polymer co-spun membrane is prepared by an electrostatic spinning process.

[0009] Furthermore, the thickness of the zeolite-polymer co-spun membrane is 0.05 mm-1 mm.

[0010] Furthermore, the polymer resin material includes one of hydrophobic polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), and polytetrafluoroethylene (PTFE).

[0011] Furthermore, the zeolite particles are uniformly dispersed in the polymer resin material to form a porous membrane structure.

[0012] Further, the porous structure includes a secondary pore structure;

[0013] The first-level pore structure includes micropores of zeolite particles, and the second-level pore structure includes pores formed by interweaving fiber filaments formed by the polymer resin material.

[0014] Furthermore, the diameter of the fiber filament is 0.5 μm-2.5 μm.

[0015] Furthermore, the preparation of the zeolite-polymer co-spun membrane includes:

[0016] The zeolite suspension is prepared by using an organic solvent;

[0017] Mixing the zeolite suspension evenly;

[0018] Using the organic solvent to prepare a polymer resin solution;

[0019] Heating and stirring the polymer resin solution to completely dissolve the polymer resin in the organic solvent;

[0020] Mixing the zeolite suspension and the polymer resin solution to obtain a mixed solution;

[0021] The mixed solution is subjected to an electrostatic spinning process to obtain a zeolite-polymer co-spinning membrane.

[0022] Furthermore, the organic solution includes one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and N-methylpyrrolidone (NMP).

[0023] Furthermore, the average particle size of the zeolite particles is less than or equal to 5 μm, and the aspect ratio of the particles is 1-1.5.

[0024] Furthermore, the average particle size of the zeolite particles is 0.5 μm-5 μm.

[0025] Furthermore, the average particle size of the zeolite particles is 0.5 μm-2 μm.

[0026] Furthermore, the mass ratio of the zeolite particles to the polymer resin is 1:4-4:1.

[0027] Furthermore, the mass ratio of the zeolite particles to the polymer resin is 1:1-3:1.

[0028] Furthermore, the zeolite particles are formed by bonding zeolites with an adhesive.

[0029] Furthermore, the adhesive includes one or more of polyacrylate, polyurethane or epoxy resin.

[0030] Furthermore, the average particle size of the zeolite particles is 150 μm-350 μm.

[0031] Furthermore, the zeolite particles in the zeolite-polymer co-spun membrane are hydrophobic zeolites.

[0032] Furthermore, the zeolite particles in the zeolite-polymer co-spun membrane are ZSM-5 zeolite materials with a high silicon-aluminum mass ratio or S-1 pure silicon zeolite materials.

[0033] Furthermore, the air permeability of the zeolite-polymer co-spun membrane is 70%-90%.

[0034] In order to solve the above technical problems, another technical solution adopted by the present invention is:

[0035] A loudspeaker, wherein the rear cavity of the loudspeaker adopts the composite material for improving the sound quality of the loudspeaker.

[0036] The beneficial effects of the present invention are as follows: a layer of zeolite-polymer co-spun membrane is coated on the surface of zeolite particles to form a composite material, which is applied to speakers. Compared with traditional spherical materials and block materials, the composite material is packaged with a flexible film material. On the one hand, the flexible film material packaging is convenient for assembly into the rear cavity of the speaker, and the flexibility of the packaging can protect the zeolite particles from being easily broken when the speaker module is powered on or subjected to a drop impact, or even if broken, the small particles of microsphere debris are not easy to leak into the speaker magnetic cavity, thereby causing abnormal sound quality of the speaker. On the other hand, by utilizing the excellent adsorption of zeolite Performance and thermal stability, zeolite materials are combined in the form of particles and membranes. The co-spun membrane material containing zeolite has an acoustic effect close to that of zeolite particles per unit weight. By co-spinning with zeolite, the membrane material itself has the effect of reducing the system resonance frequency F0. Compared with traditional membrane materials, its acoustic effect is better. Before the sound waves come into contact with the zeolite particles, they will be first tuned by the zeolite-polymer co-spun membrane. The sound waves entering the back cavity of the speaker pass through two materials with different acoustic impedances in turn to generate more energy dissipation, and finally obtain better acoustic performance, thereby further improving the sound quality of the speaker. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A schematic structural diagram of a composite material for improving the sound quality of a loudspeaker according to an embodiment of the present invention;

[0038] Figure 2 A schematic diagram of the structure of a speaker according to an embodiment of the present invention;

[0039] Figure 3 It is a comparison diagram of electrical impedance curves of the composite material of the embodiment of the present invention and the comparative example;

[0040] Figure 4 Schematic diagram of the structure of a drop tool for impact resistance testing according to an embodiment of the present invention. DETAILED DESCRIPTION

[0041] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.

[0042] The composite material and the speaker for improving the sound quality of the speaker mentioned above in the present application can be applied to various types of speakers, especially to micro speakers, such as mobile phone speakers, car speakers, etc., and are described below through specific implementation methods:

[0043] In an optional embodiment, if Figure 1 As shown, a composite material for improving the sound quality of a speaker comprises zeolite particles, wherein the zeolite particles are coated with a zeolite-polymer co-spun membrane;

[0044] That is to say, the above-mentioned composite material includes a two-layer structure, the zeolite particles constitute the inner layer structure, and the zeolite-polymer co-spun membrane constitutes the outer layer structure. This combination is placed in the back cavity of the micro-speaker to avoid the internal zeolite particles from breaking and generating noise, and can also significantly reduce the system's resonant frequency F0.

[0045] In another optional embodiment, the zeolite particles are formed by bonding zeolites by an adhesive, thereby forming zeolite microspheres;

[0046] Wherein, the adhesive includes one or more of polyacrylate, polyurethane or epoxy resin.

[0047] In another optional embodiment, the zeolite particles of the above embodiment are prepared by the following method:

[0048] (a) using deionized water as a solvent, ultrasonically dispersing zeolite in deionized water to obtain a zeolite suspension;

[0049] (b) adding an adhesive to the zeolite suspension and stirring the mixture to obtain a mixed slurry;

[0050] (c) The mixed slurry is formed into granular balls by a spray granulator, and then screened by a sieve to select particles with a particle size range of 150 μm-350 μm for drying. In an optional embodiment, particles with an average particle size of 200 μm can be screened out for drying, or particles with an average particle size of 250 μm can be dried, or particles with an average particle size of 300 μm can be dried.

[0051] In another optional embodiment, the zeolite-polymer co-spun membrane includes zeolite particles and polymer resin materials.

[0052] Wherein, the zeolite-polymer co-spun membrane is prepared by an electrostatic spinning process.

[0053] In another optional embodiment, the thickness of the zeolite-polymer co-spun membrane is 0.05 mm-1 mm. In a specific embodiment, the thickness of the zeolite-polymer co-spun membrane is 0.07 mm.

[0054] In another optional embodiment, the polymer resin material includes one of hydrophobic polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), and polytetrafluoroethylene (PTFE);

[0055] The zeolite particles in the zeolite-polymer co-spun membrane are hydrophobic zeolites.

[0056] Specifically, the zeolite particles in the zeolite-polymer co-spun membrane are ZSM-5 zeolite materials with a high silicon-aluminum mass ratio or S-1 (silicalite-1) pure silicon zeolite materials.

[0057] During use, zeolite particles will deteriorate in acoustic performance due to the adsorption of water vapor. In this embodiment, the zeolite-polymer co-spun membrane uses hydrophobic polymers and hydrophobic zeolites, which can effectively block water vapor, have better high temperature and high humidity resistance, and have higher reliability.

[0058] In an optional embodiment, the air permeability of the zeolite-polymer co-spun membrane is 70%-90%, specifically, it can be set to 80%.

[0059] In another optional embodiment, the zeolite particles are uniformly dispersed in the polymer resin material to form a porous membrane structure having at least a secondary pore structure.

[0060] In an optional embodiment, the porous structure includes a secondary pore structure;

[0061] The first-level pore structure includes micropores of zeolite particles, and the second-level pore structure includes pores formed by interweaving fibers formed by the polymer resin material;

[0062] The diameter of the fiber filament is 0.5 μm-2.5 μm, and specifically, can be set to 1 μm, 1.5 μm, 2 μm, etc.

[0063] In another optional embodiment, the preparation of the zeolite-polymer co-spun membrane comprises:

[0064] (1) A zeolite suspension is prepared by using an organic solvent, wherein the organic solvent includes one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and N-methylpyrrolidone (NMP), the average particle size of the zeolite particles is less than or equal to 5 μm, and the particle aspect ratio is 1-1.5. In an optional embodiment, the average particle size of the zeolite particles can be set to 0.5 μm-5 μm, and in another optional embodiment, the average particle size of the zeolite particles can be set to less than or equal to 2 μm, and optionally, it can be set to 0.5 μm-2 μm. Accordingly, the diameter of the fiber filament formed by the polymer resin material is set to 0.5 μm-1 μm;

[0065] (2) mixing the zeolite suspension uniformly. In an optional embodiment, the zeolite suspension can be uniformly mixed by ultrasonic dispersion and stirring;

[0066] (3) using an organic solvent such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N-methylpyrrolidone (NMP) or the like to prepare a polymer resin solution, wherein an example of the polymer resin is one of polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), polytetrafluoroethylene (PTFE) or the like;

[0067] (4) heating and stirring the polymer resin solution to completely dissolve the polymer resin in the organic solvent;

[0068] (5) mixing the zeolite suspension and the polymer resin solution to obtain a mixed solution. According to one embodiment, the mass ratio of zeolite to polymer resin in the mixed solution is in the range of 1:4-4:1. For example, if the total weight of zeolite and polymer resin in the zeolite-polymer co-spun membrane is 100%, the amount of zeolite is 20%-80%, and the amount of polymer resin is 80%-20%. Or according to other embodiments, it is in the range of 1:1-3:1.

[0069] (6) The mixed solution is subjected to an electrospinning process to obtain a zeolite-polymer co-spun membrane.

[0070] In another optional embodiment, Figure 2 As shown, a speaker, wherein the rear cavity of the speaker adopts a composite material for improving the sound quality of the speaker as described in any of the above embodiments;

[0071] The zeolite-polymer co-spun membrane and zeolite particles are used in the rear cavity of the speaker to further virtually increase the resonance volume of the rear cavity. The specific method is to load the zeolite particles wrapped by the zeolite-polymer co-spun membrane into the rear cavity of the speaker.

[0072] In this embodiment, there is no specific requirement for the size of the composite material used to improve the low-frequency sound quality of the speaker. Those skilled in the art can determine its size according to actual needs. For example, in a specific embodiment, the composite material has a total length of 5-30 mm, a total width of 1-20 mm, and a total height of 1-5 mm.

[0073] The following specific examples are used to verify the performance of the composite material for improving the sound quality of the speaker and the speaker of the present application:

[0074] First, regarding the selection of zeolite raw materials, when testing zeolite raw powders of different particle sizes and morphologies, it was found that when the particle size of the zeolite particles is 0.5μm-5μm and the particle aspect ratio is 1-1.5, the zeolite raw powder is easier to disperse in the solvent and remain uniform. If the particle size is too large, the sedimentation will be too fast; if the particle size is too small, the zeolite particles will be difficult to disperse in the solvent; in addition, if the aspect ratio is too large, the slurry viscosity will be too high and the fluidity of the slurry will be poor, affecting the subsequent ball-forming and film-forming processes. In view of this, the present embodiment uses zeolite raw materials with a zeolite particle size of 0.5μm-5μm and a particle aspect ratio of 1-1.5;

[0075] Correspondingly, the diameter of the fiber filaments formed by the polymer resin material is set to 0.5 μm-2.5 μm;

[0076] The range of zeolite particle size corresponds to the range of fiber diameter. If the particle size is much smaller than the fiber diameter, there is a high probability that the zeolite will be completely wrapped by the fiber and unable to contact the air, resulting in the inability of the zeolite's own micropores to play a gas adsorption-desorption role, thereby affecting its acoustic effect. If the zeolite particle size is too large and the fiber is too thin, the zeolite-polymer co-spun fiber is very fragile and easy to break, and debris will be generated during use, resulting in problems with the reliability of the material.

[0077] ZSM-5 zeolite particles with a silicon-aluminum mass ratio of about 90 (analyzed by X-ray fluorescence spectroscopy) and a particle size distribution of 0.5μm-2μm and a polyacrylate adhesive were selected, and the particles were prepared by spray granulation and particles with a particle size of 150μm-350μm were screened out. Finally, they were dried at 120°C for 2 hours to obtain zeolite particles.

[0078] Zeolite-polymer co-spun membrane air permeability test: refer to GBT5453, zeolite-polymer co-spun membrane air permeability test, test pressure 200Pa, sample membrane area 100cm 2 , record the sample film thickness.

[0079] Zeolite-polymer co-spun membrane fiber diameter: Through scanning electron microscopy testing, the fiber diameter data was measured and statistically analyzed in the selected SEM field of view.

[0080] Example 1

[0081] Step 1, the same particle size of 0.5μm-5μm, particle aspect ratio of 1-1.5 ZSM-5 zeolite (silicon aluminum mass ratio of about 1100, using X-ray fluorescence spectroscopy analysis), the zeolite particles and the polymer resin polyvinylidene fluoride (PVDF) are dispersed in a dimethylformamide solution, and the electrospinning method is used: the electrospinning voltage is set to 20kv, the spinning needle is 0.3mm, and the electrospinning wheel speed and spinning time are adjusted to prepare a zeolite-polymer fiber membrane with a thickness of 0.1mm and a fiber diameter range of 0.5μm-2.5μm, and then it is dried at 120°C for 2 hours to obtain a zeolite-polymer co-spun membrane with an air permeability of 89.14%.

[0082] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with zeolite-polymer co-spun membrane to form small cubes of 10*15*2 mm.

[0083] Example 2

[0084] Step 1. Also select ZSM-5 zeolite with a particle size of 0.5μm-5μm and a particle aspect ratio of 1-1.5 (silicon-aluminum mass ratio of about 1100, analyzed by X-ray fluorescence spectroscopy), disperse the zeolite particles and the polymer resin polyvinylidene fluoride (PVDF) in a dimethylformamide solution, and use the electrospinning method: the electrospinning voltage is set to 20kv, and the spinning needle is 0.3mm. By adjusting the electrospinning wheel speed and spinning time, a zeolite-polymer fiber membrane with a thickness of 0.2mm and a fiber diameter range of 0.5μm-2.5μm is prepared, and then it is dried at 120°C for 2 hours to obtain a zeolite-polymer co-spun membrane with an air permeability of 86.81%.

[0085] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with zeolite-polymer co-spun membrane to form small cubes of 10*15*2 mm.

[0086] Example 3

[0087] Step 1. Also select ZSM-5 zeolite with a particle size of 0.5μm-5μm and a particle aspect ratio of 1-1.5 (silicon-aluminum mass ratio of about 1100, analyzed by X-ray fluorescence spectroscopy), disperse the zeolite particles and polymer resin polyvinylidene fluoride (PVDF) in a dimethylformamide solution, and use electrospinning: the electrospinning voltage is set to 20kv, and the spinning needle is 0.3mm. By adjusting the electrospinning wheel speed and spinning time, a zeolite-polymer fiber membrane with a thickness of 0.5mm and a fiber diameter range of 0.5μm-2.5μm is prepared, and then it is dried at 120°C for 2 hours to obtain a zeolite-polymer co-spun membrane with an air permeability of 80.34%.

[0088] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with zeolite-polymer co-spun membrane to form small cubes of 10*15*2 mm.

[0089] Example 4

[0090] Step 1. Also select ZSM-5 zeolite with a particle size distribution of 0.5-5um and a particle aspect ratio of 1-1.5 (silicon-aluminum mass ratio of about 1100, analyzed by X-ray fluorescence spectroscopy), disperse the zeolite particles and polymer resin polyvinylidene fluoride (PVDF) in a dimethylformamide solution, and use electrospinning: the electrospinning voltage is set to 20kv, and the spinning needle is 0.3mm. A zeolite-polymer fiber membrane with a thickness of 1mm and a fiber diameter range of 0.5-2.5um is prepared, and then it is dried at 120°C for 2 hours to obtain a zeolite-polymer co-spun membrane with an air permeability of 71.58%.

[0091] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with zeolite-polymer co-spun membrane to form small cubes of 10*15*2 mm.

[0092] Example 5

[0093] Step 1. Also select S-1 zeolite (all-silica zeolite) with a particle size distribution of 0.5-5um and a particle aspect ratio of 1-1.5, disperse the zeolite particles and the polymer resin polyvinylidene fluoride (PVDF) in a dimethylformamide solution, and use the electrospinning method: the electrospinning voltage is set to 20kv, and the spinning needle is 0.3mm. By adjusting the electrospinning wheel speed and spinning time, a zeolite-polymer fiber membrane with a thickness of 0.2mm and a fiber diameter range of 0.5-2.5um is prepared, and then it is dried at 120°C for 2 hours to obtain a zeolite-polymer co-spun membrane with an air permeability of 88.98%.

[0094] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with zeolite-polymer co-spun membrane to form small cubes of 10*15*2 mm.

[0095] Comparative Example 1

[0096] Step 1: Without adding zeolite, only disperse the polymer resin polyvinylidene fluoride (PVDF) in a dimethylformamide solution, and use the electrospinning method: the electrospinning voltage is set to 20kv, and the spinning needle is selected to be 0.3mm. A polymer fiber membrane with a thickness of 0.2mm and a fiber diameter range of 0.5-2.5um is prepared, and then it is dried at 120°C for 2 hours to obtain a polymer porous membrane with an air permeability of 90.47%.

[0097] Step 2: Weigh 150 mg of zeolite particles and completely wrap them with ordinary fiber membranes into small cubes of 10*15*2 mm.

[0098] Comparative Example 2

[0099] Weigh 150 mg of zeolite particles.

[0100] Acoustic F0 test:

[0101] according to Figure 2 As shown in the structural schematic diagram, the zeolite materials in the above-mentioned embodiment and the comparative example are respectively placed in the rear cavity of the audio speaker to perform acoustic impedance testing, and the impedance curve of the zeolite material is measured as follows Figure 3 As shown, by comparing the difference in the resonant frequency F0 of the speaker before and after placing the zeolite material, the resonant frequency F0 reduction value of the speaker is obtained. The test results are as follows:

[0102] Table 1 Comparison of composite materials on the reduction of loudspeaker resonance frequency

[0103]

[0104] By comparing Example 2, Comparative Example 1 and Comparative Example 2, it is not difficult to find that the zeolite particle structure wrapped with a zeolite-polymer co-spinning membrane reduces the resonant frequency of the speaker more than the zeolite particles wrapped with ordinary fibers and the particles not wrapped with fiber membranes. This is because, like the principle of zeolite particles reducing the resonant frequency of the speaker, the fiber membrane with zeolite added also has a rich microporous channel structure and a specific surface area far exceeding that of ordinary fibers. In addition, acoustics dissipate energy through the fiber membrane, and sound energy is converted into heat energy. Rapid heat conduction can be achieved through the fiber, converting the original adiabatic process of the speaker system into an isothermal process, which can effectively reduce the resonant frequency F0 of the system.

[0105] It can be seen from Examples 1-4 that as the thickness of the zeolite-polymer co-spun membrane changes, the resonant frequency drop value of the test increases first and then decreases. The first increase is because the thickness of the zeolite-polymer co-spun membrane increases, which is equivalent to adding more zeolite-polymer co-spun membranes with sound-absorbing effects in the back cavity, which will lead to improved acoustic performance. As the thickness of the zeolite-polymer co-spun membrane further increases, its air permeability will decrease, and its resistance to air circulation will increase, which will cause the acoustic compliance of the speaker back cavity to decrease, and in turn, the effect of the material in reducing F0 will deteriorate.

[0106] High temperature and high humidity resistance test

[0107] Place Examples 1 to 5 and Comparative Examples 1 and 2 in a high temperature and high humidity test box, set the temperature to 85°C and the humidity to 85% RH, leave it for 168 hours, take it out and let it stand at room temperature for 2 hours. Take out the 150 mg zeolite particles wrapped in Examples 1 to 5 and Comparative Example 1, and then perform an F0 test on these zeolite particles, and compare the changes in the F0 reduction values ​​of these zeolite particles before and after high temperature and high humidity aging. Since the zeolite particle formulas of all embodiments are consistent, the initial F0 of the zeolite particles adopts the test data of Comparative Example 2. The test results are shown in Table 2:

[0108] Table 2 Comparison of high temperature and high humidity resistance test results

[0109]

[0110]

[0111] It can be seen from Table 2 that, compared with Comparative Example 2, Comparative Example 1 uses a hydrophobic polymer fiber membrane, which well protects the internal zeolite particles from being invaded by water vapor, and the aging failure rate is reduced. As the thickness of the zeolite-polymer co-spun membrane increases in Examples 1, 2, 3, and 4, the air permeability decreases, water vapor is less likely to penetrate, and the internal zeolite particles are almost ineffective. Compared with Example 2, the zeolite-polymer co-spun membrane in Example 5 uses a more hydrophobic S-1 zeolite. Although the thickness is only 0.2 mm, its ability to protect the internal zeolite particles is comparable to the thicker zeolite-polymer co-spun membrane in Example 3.

[0112] Impact resistance test:

[0113] The composite materials prepared in the above examples 1-5 were subjected to a drop test, and their structural schematic diagrams are shown in FIG. Figure 4 The drop test is as follows:

[0114] 1) The composite materials prepared in Examples 1-5 were loaded into a micro-speaker back cavity as test samples, wherein the volume of the speaker back cavity was 1 cubic centimeter.

[0115] 2) Assemble the speaker in an aluminum alloy box with a size of 150×75×10 mm (to simulate the use environment of the sound-absorbing composite material in a mobile phone); and add a weight of 150 g to each dropped test sample.

[0116] 3) Lift the test sample to a drop height of 1500mm (drop height refers to the distance between the lowest point of the sample and the impact table when ready to be released) and support it in a predetermined state. The difference between the lifting height and the predetermined height shall not exceed ±2% of the predetermined height.

[0117] 4) Select the longest edge and the largest surface of the aluminum alloy box as the drop test object; first drop the corner, then drop the edge, and finally drop the surface according to the predetermined state of one corner, three edges and six faces (the corner, edge and surface drop are tested once respectively as a group of experiments), wherein the following conditions need to be met during the drop:

[0118] (a) When dropped at an angle, the angle between the specified surface of the test specimen and the impact table is within ±5° or 10% of this angle (whichever is greater), so that the gravity line of the test specimen passes through the dropped corner;

[0119] (b) When the edge is dropped, the maximum angle between the dropped edge and the horizontal plane does not exceed 2°, and the error between the specified surface of the test sample and the impact table surface is not greater than ±5° or 10% of this angle (whichever is greater), so that the gravity line of the test sample passes through the dropped edge;

[0120] (c) When the test sample is dropped on a flat surface, the angle between the drop surface and the horizontal plane should not exceed 2°; so that the gravity line of the test sample passes through the drop surface;

[0121] (d) The difference between the actual impact velocity and the impact velocity during free fall does not exceed ±1% of the free fall velocity.

[0122] Impact resistance test of the control group

[0123] Comparative Example 1 and Comparative Example 2 were tested for impact resistance according to the above steps.

[0124] The drop test results of the samples in each embodiment group and the control group after the drop are recorded, and the recorded results are as follows:

[0125] Table 3 Composite material drop test results

[0126]

[0127] Based on the test results shown in Table 3 above, it is not difficult to find that the zeolite particles wrapped by the membrane material are more impact-resistant and less likely to break, and the membrane material can effectively prevent the overflow of broken particles.

[0128] In summary, the present invention provides a composite material and a speaker for improving the sound quality of a speaker, wherein the zeolite material is combined and coordinated in the form of particles and membranes. On the one hand, the zeolite-polymer co-spun membrane is soft and breathable, and can well protect the hard zeolite particles, so that the zeolite particles can be well protected during tooling drop and power-on reliability tests (at this time, the zeolite particles will vibrate in the rear cavity of the speaker and continuously hit the rear cavity wall of the speaker, which may cause breakage and enter the magnetic cavity, resulting in abnormal sound quality); on the other hand, the zeolite particles will absorb water vapor during use, resulting in acoustic The performance is deteriorated, while the zeolite-polymer co-spun membrane adopts hydrophobic polymer and hydrophobic zeolite, which can block water vapor and has better high temperature and high humidity resistance. At the same time, the zeolite-polymer co-spun membrane itself has the effect of reducing the system resonance frequency F0, and compared with the method of packaging with porous mesh cloth, it can obtain better acoustic advantages. Moreover, before the sound waves come into contact with the zeolite particles, they will be first tuned by the zeolite-polymer co-spun membrane. The sound waves entering the back cavity of the speaker will pass through two materials with different acoustic impedances in turn to generate more energy dissipation, and finally obtain better acoustic performance, which can effectively improve the sound quality of the speaker.

[0129] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A composite material for improving the sound quality of a speaker, comprising zeolite particles, characterized in that: The zeolite particles are coated with a zeolite-polymer co-spun membrane on the outside.

2. A composite material for improving the sound quality of a loudspeaker according to claim 1, characterized in that: The zeolite-polymer co-spun membrane comprises zeolite particles and polymer resin materials.

3. A composite material for improving the sound quality of a loudspeaker according to claim 1 or 2, characterized in that: The zeolite-polymer co-spinning membrane is prepared by an electrostatic spinning process.

4. A composite material for improving the sound quality of a loudspeaker according to claim 1 or 2, characterized in that: The thickness of the zeolite-polymer co-spun membrane is 0.05 mm-1 mm.

5. The composite material for improving the sound quality of a loudspeaker according to claim 2, characterized in that: The polymer resin material includes one of hydrophobic polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), and polytetrafluoroethylene (PTFE).

6. The composite material for improving the sound quality of a loudspeaker according to claim 2, characterized in that: The zeolite particles are uniformly dispersed in the polymer resin material to form a porous membrane structure.

7. The composite material for improving the sound quality of a loudspeaker according to claim 6, characterized in that: The porous structure includes a secondary pore structure; The first-level pore structure includes micropores of zeolite particles, and the second-level pore structure includes pores formed by interweaving fiber filaments formed by the polymer resin material.

8. The composite material for improving the sound quality of a loudspeaker according to claim 7, characterized in that: The diameter of the fiber filament is 0.5 μm-2.5 μm.

9. A composite material for improving the sound quality of a loudspeaker according to any one of claims 1, 2 and 5 to 8, characterized in that: The preparation of the zeolite-polymer co-spun membrane comprises: The zeolite suspension is prepared by using an organic solvent; Mixing the zeolite suspension evenly; Using the organic solvent to prepare a polymer resin solution; Heating and stirring the polymer resin solution to completely dissolve the polymer resin in the organic solvent; Mixing the zeolite suspension and the polymer resin solution to obtain a mixed solution; The mixed solution is subjected to an electrostatic spinning process to obtain a zeolite-polymer co-spinning membrane.

10. The composite material for improving the sound quality of a loudspeaker according to claim 9, characterized in that: The organic solution includes one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and N-methylpyrrolidone (NMP).

11. The composite material for improving the sound quality of a loudspeaker according to claim 9, characterized in that: The average particle size of the zeolite particles is less than or equal to 5 μm, and the aspect ratio of the particles is 1-1.

5.

12. The composite material for improving the sound quality of a loudspeaker according to claim 11, characterized in that: The average particle size of the zeolite particles is 0.5 μm-5 μm.

13. The composite material for improving the sound quality of a loudspeaker according to claim 12, characterized in that: The average particle size of the zeolite particles is 0.5 μm-2 μm.

14. A composite material for improving the sound quality of a loudspeaker according to any one of claims 10 to 13, characterized in that: The mass ratio of the zeolite particles to the polymer resin is 1:4-4:

1.

15. The composite material for improving the sound quality of a loudspeaker according to claim 14, characterized in that: The mass ratio of the zeolite particles to the polymer resin is 1:1-3:

1.

16. A composite material for improving the sound quality of a speaker according to any one of claims 1 to 2 and 5 to 8, characterized in that: The zeolite particles are formed by bonding zeolites via an adhesive.

17. The composite material for improving the sound quality of a loudspeaker according to claim 16, characterized in that: The adhesive includes one or more of polyacrylate, polyurethane or epoxy resin.

18. A composite material for improving the sound quality of a speaker according to any one of claims 1 to 2, 5 to 8 and 10 to 13, characterized in that: The average particle size of the zeolite particles is 150 μm-350 μm.

19. A composite material for improving the sound quality of a loudspeaker according to any one of claims 1 to 2 and 5 to 8, characterized in that: The zeolite particles in the zeolite-polymer co-spun membrane are hydrophobic zeolites.

20. The composite material for improving the sound quality of a loudspeaker according to claim 19, characterized in that: The zeolite particles in the zeolite-polymer co-spun membrane are ZSM-5 zeolite materials with a high silicon-aluminum mass ratio or S-1 pure silicon zeolite materials.

21. A composite material for improving the sound quality of a speaker according to any one of claims 1, 2 and 5 to 8, characterized in that: The air permeability of the zeolite-polymer co-spun membrane is 70%-90%.

22. A loudspeaker, characterized in that: The speaker back cavity adopts a composite material for improving the sound quality of the speaker as claimed in any one of claims 1 to 21.